Семантичне калькування в галузі української науково-технічної термінології - Кримець, Оксана Михайлівна (Харківський національний педагогічний університет імені Г. С. Сковороди, 2025)
Робота присвячена семантичному калькуванню як одному зі шляхів розвитку української науково-технічної термінології. Калькування розглянуто як спосіб запозичення термінів з інших мов, за якого мовою-реципієнтом сприймається і значення, і принципи побудови іншомовного терміна. Виокремлено типи термінів-кальок на базі спеціальних назв сфери ІТ‑технологій та кібербезпеки. Досліджено зміни, що відбуваються у значеннях слів мови-реципієнта в процесі семантичного калькування, результатом якого є розширення семантичного потенціалу лексичних одиниць української мови, тобто поява нових термінологічних значень. The article examines calquing as a method of creating new terms, in which the meaning and organisational principle of a foreign-language unit are assimilated and conveyed through the means of the Ukrainian language. The primary focus is on the current issue of semantic calquing of IT and cybersecurity terminology, which has not been addressed in academic research yet. The study aims to analyse terms borrowed through calquing, their classification, and the identification of the essence and nature of semantic calque terms. The objective is to establish the mechanisms of semantic transformations and to identify specific processes that occur during the borrowing of terms through semantic calquing. Based on specialised vocabulary in the field of IT and cybersecurity, certain types of calque terms are distinguished: one-word (derivational/semantic) and multi-word (full and partial calques) types. The study explores purely semantic calque terms that acquired specialised meaning under the influence of foreign-language terms. It has been found that in the field of IT and cybersecurity, semantic calque terms emerge as literal translations of English specialised terms: abuser – зловмисник, attacker – нападник, bridge – міст, comb – гребінець, infringer – порушник, key – ключ, and others. It has been established that there is equivalence between the terms of the recipient language and the source language at the level of original meanings. In contrast, the new terminological meaning is a result of a transfer that developed due to foreign-language influence. In such cases, processes of secondary nomination occur within the semantic structure of the word in the recipient language. New terminological meanings are acquired not only by commonly used native words, but also by words and terms that had previously entered the Ukrainian language through direct borrowing and later, as a result of semantic calquing, obtained terminological meanings in the field of IT and cybersecurity: bank – банк, client – клієнт, contention – конфлікт, and others. It is determined that semantic calquing is one of the productive methods of term formation in IT and cybersecurity. It does not lead to the emergence of new lexical units. Still, it contributes to the expansion of the semantic potential of existing com monly used words and terms in the Ukrainian language.
Semantic calquing in ukrainian scientific and technical terminology
Keywords: термін; запозичення термінів; калькування; семантичне калькування; мова-продуцент; мова-реципієнт; вторинна номінація; семантичні перетворення; term; term borrowing; calquing; semantic calquing; source language; recipient language; secondary nomination; semantic transformations